Curriculum innovation in tourism training: a conceptual-theoretical approach - Castillo-Palacio, Marysol; Ardila, Luz Marina; Castrillón, Andrés José (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Changes in the environment call for the transformation of tourism training curricula from traditional to holistic, balancing theory and practice and including the development of soft skills and the use of technological tools. This theoretical-conceptual article seeks to identify the competencies, skills and characteristics suggested in tourism training, and to describe the general research trends on curricular innovation in tourism. An analysis of academic scientific articles extracted from the Scopus and Science Direct databases between 2008 and 2018 is made.